A Meta-Synthesis of the Integrated Model of Customer Value co-Destruction and Value co-Creation - Zohreh Dehdashti Shahrokh; Vahid Nasehifar; Mohammad Reza Karimi Alavijeh; Yazdan Rahmatabadi (پژوهش‌های مدیریت عمومی)
Abstract Considering that the Internet and the advancement of technology have created very advanced infrastructures for the interaction between organizations and customers, and both value creation and value destruction are two inseparable components of the relationship between the customer and the organization and the interactive process between the two. Two general issues have been examined and researched in this research, firstly, there is no integrated and comprehensive point of view regarding co-destruction and synergy of value, and secondly, the definition of co-destruction of customer value, which is defined as inefficiency of co-creation, should be changed. Redefine this term. In this research, by examining 157 articles using a meta-combination method based on the Hoon model, the results were obtained that the co-destruction of customer value precedes the co-creation of customer value, and in order for organizations to create co-creation of customer value, first of all, there is a need for its inhibiting factors, i.e. Identify the factors that cause the co-destruction of customer value and take steps to improve the value perceived by the customer by using appropriate strategies to control these factors so that ultimately the co-creation of customer value is created. In this regard, it is possible to redefine both creation and destruction of customer value, and appropriate measures to reduce the wastage of financial, time and credit resources can be put on the agenda.  Introduction The main problem that is trying to be addressed is that these sharing economy platform companies with the hope of successfully co-creating value start processing different ideas and expect to receive appropriate feedback from this, which leads to co-destruction for different reasons. And because there is no unified view of this issue, the methods of dealing with this issue are not clear and there is not enough information in this field. This is despite the fact that the managers are not aware of the existence and how to create the co-destruction of customer value and it is expected that if they are aware of this mechanism, they will formulate the processes in such a way that the methods of restraining the co-destruction of customer value and prevent deviation from the company's activities It is determined and the company is led to create co-creation.Case study Given that the sharing economy industries in the country are increasing and growing significantly, it is very important and significant to study these industries. For this reason, companies such as SNAPP and TAPSI, which have the largest market share in the car rental industry with a driver, can be considered as a case study. These companies have repeatedly tried to create value for customers using various technologies, but this has caused them to encounter numerous problems and even turn the aforementioned activity into an anti-brand event for them. In this regard, it should be borne in mind that both value creation and value destruction are two inseparable aspects of the cooperation processes between the organization and the customer, and there is a thin line between the two. One of the cases where value co-creation has been transformed into co-destruction can be considered when women request a car, in which cases the driver is also considered a woman. This has caused some drivers or even passengers to abuse this and engage in illegal activities, and many problems have occurred in this regard. Therefore, the intended co-creation for the customer becomes a co-destruction of value, and the organization suffers from this. Organizations should pay more attention to this area and ultimately create the best outcome for themselves.Materials and Methods Various methods are used to conduct meta synthesis research, which can be the methods of Walsh and Dunn in 2005, Sandolski and Barroso, whose prototype was presented in 2003 and its update in 2007, and finally the model presented by Hohn in 2013 pointed out that this model was developed based on Walsh and Dunn's model. In this research, the Hun model has been used because this model has used modern methods and comprehensively used previous models, and it can increase the validity and reliability of the research in a documented way and with reasoning from a specific path and with correct logic.Discussion and Results Finally, the achievement of this research is presented in the description of the following model, which at the two levels of customers and organizations, the variables "creating factors of customer value co-destruction", "customer value co-destruction", "customer value co-destruction containment strategies", "value perceived by customer" and finally "customer value co-creation" appear. The variable "Customer Perceived Value", which is the only variable appearing at the customer level, is shown in the figure with a dashed line. It should be noted that all the variables appear in both levels, but they show the greatest impact in the mentioned levels.ConclusionIt is very important to keep in mind that the categories of both value creation and destruction have a semantic contradiction, but it is necessary to pay attention to the fact that the creation of customer value co-destruction is unavoidable and the processes tend to increase entropy and disorder. This is also true regarding the co-destruction of customer value and the tendency of the system to create co-destruction is that by identifying the factors that cause co-destruction and curbing them using the appropriate strategy, it will be possible to create co-creation continuously and continuously. In fact, the model presented in this research shows that in order to create co-creation, one must first identify co-destruction, find a suitable strategy to control it, and finally have a good impact on the value perceived by the customer in order to create co-creation. To be created sustainably. According to the findings of this research, the success of co-creation depends on the correct control of the destruction of customer value.